Chilblain-like lesions in a pediatric patient - Alba, Diana; Cascais, Inês; Moreira, Mafalda; Ribeiro, Maria Céu; Abreu Ferreira, Jorge (BIRTH AND GROWTH MEDICAL JOURNAL, 2023)
COVID-19 usually has a mild course in the pediatric population. Several cutaneous manifestations of the condition have been reported, being chilblain-like lesions one of the most common in younger ages. These may manifest as erythematous or violaceous macules, mostly involving the toes and feet, but less frequently also the fingers and hands. These patients usually have a favorable outcome, with complete spontaneous regression of lesions and no complications. The authors report the case of a 12-year-old female patient who presented to the Emergency Department with cutaneous lesions suggestive of chilblains and a diagnosis of COVID-19 infection 17 days earlier.